New Media : Instagram @bolalobfootball Sebagai Media Informasi Sepakbola Masyarakat Kota Tangerang - Singgih Berlan Kosasi; Engga Probi Endri (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
Instagram social media is a new media that is currently used by the public in finding and getting information. One of them is the social media Instagram @bolalobfootball which is used by the People of Tangerang City as a source of football information. The style of language, type of information and features used by Instagram @bolalobfootball in conveying football information enjoyed by the people of Tangerang City varies. This research aims to find out how Instagram @bolalobfootball as a source of football information for the people of Tangerang City. The study uses the foundation of the Media Richness Theory by Littlejohn. The paradigm used in this research is constructivism, with qualitative case study research methods. The study subjects consisted of five people from Tangerang City who have a vulnerable age of 20- 29 years, follow Instagram @bolalobfootball for at least one year, and like five posts from Instagram @bolalobfootball in one day. The result of this study is that Instagram @bolalobfootball able to meet the information needs of informants and viewed from the point of view of Media Rrichness Theory Instagram @bolalobfootball managed to meet four factors measuring the wealth of a media. The conclusion of this study is that Instagram @bolalobfootball with the use of Instagram features, the style of language used, the type of information provided is able to meet the football information needs of the people of Tangerang City.